Influence of high-frequency magnetic fields on the noise behavior of CMS 2S module prototypes. (1st January 2023) - Dziwok, C.; Feld, L.; Klein, K.; Lipinski, M.; Pauls, A.; Pooth, O.; Röwert, N.; ,
Abstract: For the CMS tracker Phase-2 upgrade new modules with silicon strip sensors are being developed.Each module features a Service Hybrid (SEH), which is responsible for the distribution of low voltages to the module components using a two-stage DC-DC conversion scheme.For modules equipped with the latest generation of SEHs an increase in module noise has been observed.A setup for inducing radiative noise with external magnetic fields that are frequency- and location-dependent is presented.Measurements carried out on modules from different prototyping phases show that the sensitivity is similar across generations, which indicates that radiative coupling into the sensor or readout electronics is not responsible for the observed noise increase.